Nekaj geografskih značilnosti biotehnoloških podjetij v Sloveniji - Drofenik, Urh (Geografski obzornik, 2023)
Biotechnology is a recent industry that uses living organisms to modify living or nonliving matter for the purpose of producing knowledge, goods, and services. In this article, we highlight the main geographical characteristics of biotechnology and show the centers of biotechnology in the United States of America and the European Union. We have registered 85 companies in the field of biotechnology in Slovenia. The companies are mainly concentrated in the areas of Central Slovenia and Ajdovščina-Nova Gorica. The recent development of biotechnology will promote the development of a biotechnology cluster in Slovenia.
Keywords: biotechnology; biotehnologija; economic geography; ekonomska geografija; Slovenia; Slovenija